The role of awareness in appraising the success of E-government systems - Imdadullah Hidayat Ur Rehman; Jamshid Ali Turi; Joanna Rosak-Szyrocka; Mohammad Nurul Alam; Ladislav Pilař (Cogent Business & Management, 2023)
Worldwide governments are launching e-government (E-Gov) systems to ensure the superior delivery of services to their citizens. Ensuring the success of government-to-citizen (G2C), E-Gov systems is still challenging for various developing countries. To overcome this challenge, investigating the success of G2C E-Gov systems is important. This paper assesses the success of E-Gov systems from the perspective of a developing country. For this purpose, this research incorporates perceived-usefulness and perceived-trust variables into DeLone and McLean's IS success model. A survey-based method was employed to collect data from Pakistani citizens. The PLS-SEM method was used for the validation of the conceptual model. Using the non-probability sampling technique, a sample of 264 usable cases was collected and used to analyze our model. It is evident from the outcomes of the study that information-quality has significant effects on the use of E-Gov and user-satisfaction, while service-quality, system-quality, and perceived-trust have significant effects on the use of E-Gov, user-satisfaction and perceived-usefulness. Further, the use of E-Gov, perceived-usefulness, and user-satisfaction have direct, significant impacts on the perceived-net-benefits. The practitioners are recommended to concentrate on the three quality dimensions i.e. information quality, system quality, and service quality while preparing E-Gov applications. The role of governments is also important to launch awareness campaigns and motivate their citizens to use E-Gov services.
Keywords: 650; service quality; perceived usefulness; DeLone and McLean’ s IS success model; E-Government systems; information quality; information systems; system quality